Implementasi Penyelenggaraan Pendidikan Inklusif Di Kabupaten Situbondo: (Studi Pada Sd Negeri 2 Kilensari) - Yuliyanto, Yuda; Sedarmayanti (Soetomo Magister Ilmu Administrasi, 2023)
Name of the researcher Yuda Yuliyanto, NIM. 202242930078, Public Administration Master’s Study Program, Faculty of Administrative Sciences. This study is entitled "The Implementation of Inclusive Education in Situbondo Regency". The background of the study is that there are apparently many children with disabilities or children with special needs who have not had the opportunity to obtain education in elementary schools. Hence, this condition creates various obstacles e.g. the social conditions of the community, insufficient facilities and infrastructure and also the absence of teachers who are specifically assigned for those with disabilities and special needs. Another obstacle comes from the school that organizes inclusive education. Those schools have not been able to optimally organize inclusive education. In short, the inclusive education is still not well-developed. Therefore, the main research problem is "How is the Implementation of Inclusive Education in Situbondo Regency?" The main purpose of this study is to find out the implementation of inclusive education in Situbondo Regency and what are the supporting and inhibiting factors for the implementation of inclusive education at the Regional Education and Culture Office of Situbondo. The results of this study can contribute ideas for local governments, regional education and culture offices, education managers in organizing a better inclusive education delivery system and provide wider information for the community regarding the implementation of inclusive education. This study used qualitative methods. The data collection process was carried out using observation techniques, in-depth interviews, and documentation studies. In analyzing the data, the researcher used qualitative analysis techniques in collecting the data, reducing the data, presenting the data presentation, and drawing conclusion. The data validation is carried out through the degree of trust (credibility), transferability, dependability, and certainty (confirmability). The results of this study show (1) the implementation of inclusive education in Situbondo Regency is still not optimal and equitable, (2) the Inclusive Education curriculum still uses the KTSP (the 2006 school-level autonomy curriculum), (3) the lack of facilities and infrastructure to accommodate students with special needs, (4) the absence of a special assistant teacher, (5) the absence of evaluation and monitoring from the authorities to schools that organize inclusive education, and (6) the supporting factors for the implementation of Inclusive Education is the involvement of all parties related to Inclusive Education are lacking. Further, the role of principals, teachers and parents is very decisive in fostering student character. Keywords: Implementation of Inclusive Education